Australia’s Crisis Responses During COVID-19: The Case of International Students - Qi, Jing; Ma, Cheng (Journal of International Students, 2021)
Since the outbreak of the COVID-19 pandemic, the global international education sector has been fraught with multiple, intensifying stressors, which have severely affected international students’ lives and study. Host government policies on international education can make a critical difference for this vulnerable population during the pandemic. Australia’s crisis response policies during the pandemic have been closely tracked and vigorously discussed amongst Chinese international students. This study examines how Australia’s crisis responses addressed the needs of international students during the pandemic, and how these policies impacted Chinese international students’ experiences and perceptions of studying in Australia. We collected qualitative data through interviews with Chinese international students, parents and migration agents, virtual ethnography on WeChat, and analysis of Australia’s policy responses. Our thematic analysis highlights participants’ experiences and views of Australia’s crisis responses in the four areas of financing, third-country transit, visas and immigration, and pandemic management. We discuss these findings in relation to the historical context of Australia’s higher education funding reforms during the 1980s and 1990s.